Absolute configuration of an axially chiral sulfonate determined from its optical rotatory dispersion, electronic circular dichroism, and vibrational circular dichroism spectra. Issue 11 (18th August 2017) - Covington, Cody L.; Raghavan, Vijay; Smuts, Jonathan P.; Armstrong, Daniel W.; Polavarapu, Prasad L.
Abstract: The absolute configuration (AC) of an axially chiral sulfonate (aCSO), 3, 5‐dimethyl‐2‐(naphthalen‐1‐yl)‐6‐(naphthalen‐1‐yl)benzenesulfonate (labeled as aCSO5), was investigated using optical rotatory dispersion (ORD), electronic circular dichroism (ECD), and vibrational circular dichroism (VCD) spectroscopies. All three methods led to the same conclusion and the AC of aCSO5 is reliably determined to be (−)‐(a R, a R ), or conversely (+)‐(a S, a S ). Abstract :